ВПЛИВ АВТОМАТИК ЕНЕРГОБЛОКІВ АЕС НА СТІЙКІСТЬ ЗА ЧАСТОТОЮ ПРИ ПОДІЛІ ОЕС УКРАЇНИ НА ДВА ІЗОЛЬОВАНО ПРАЦЮЮЧИХ ОСТРОВИ - Стелюк, A.O. (Інститут електродинаміки НАН України, Київ, 2016)
The frequency change has been considered in the event of the parallel and isolated operation of the interconnected power system (IPS) of Ukraine. The frequency automatics operation of the nuclear power plant generators is analyzed in case of the emergency. The methodology has been proposed for the different operation conditions considering IPS of Ukraine separation into two islands at “Zakhid-Vinnytsa” interface. The simulation results considering frequency load shedding and frequency automatics of the power units are shown for such disturbance. References 3, figures 4.